2008
DOI: 10.1016/j.bbamcr.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure influences the sensitivity of DNA to γ-radiation

Abstract: For the first time, DNA double-strand breaks (DSBs) were directly visualized in functionally and structurally different chromatin domains of human cells. The results show that genetically inactive condensed chromatin is much less susceptible to DSB induction by gamma-rays than expressed, decondensed domains. Higher sensitivity of open chromatin for DNA damage was accompanied by more efficient DSB repair. These findings follow from comparing DSB induction and repair in two 11 Mbp-long chromatin regions, one wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
124
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(147 citation statements)
references
References 54 publications
15
124
2
1
Order By: Relevance
“…Since we cannot exclude the presence of less dense patches of DNA at the periphery of the nucleolus, this result highlights the sensitivity of our method with respect to chromatin structure. The observation is also consistent with the reduced susceptibility to damage and slower decondensation of highly compacted chromatin regions supporting the validity of our approach [25][26][27]. Our data are also in accordance with the slower kinetics and less efficient DNA repair in heterochromatin as compared to euchromatin [28].…”
Section: Resultssupporting
confidence: 90%
“…Since we cannot exclude the presence of less dense patches of DNA at the periphery of the nucleolus, this result highlights the sensitivity of our method with respect to chromatin structure. The observation is also consistent with the reduced susceptibility to damage and slower decondensation of highly compacted chromatin regions supporting the validity of our approach [25][26][27]. Our data are also in accordance with the slower kinetics and less efficient DNA repair in heterochromatin as compared to euchromatin [28].…”
Section: Resultssupporting
confidence: 90%
“…The loss of accessibility is accompanied by a gain of H3, indicating that the progressively occurring chromatin compaction is achieved either by active chromatin remodeling or incorporation of new nucleosomes. Although previous studies have suggested that heterochromatic regions are less prone to DNA damage in response to ionizing irradiation, γ-rays or chemical agents (Falk et al, 2008;Seo et al, 2012;Takata et al, 2013; Wei Yu, Genome-wide analysis of DNA damage and repair, Technische Universität Darmstadt, PhD thesis, 2014), our and other published data indicate that UV-induced DNA damage might occur both in eu-and hetero-chromatic regions (Wei Yu, Genome-wide analysis of DNA damage and repair, Technische Universität Darmstadt, PhD thesis, 2014; Zavala et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, chromatin condensation has been reported to protect DNA from damaging radiation, and decondensation (not necessarily transcription-related) is sufficient to sensitize DNA to radiation (59,60). A proposed mechanism for this phenomenon is that condensation of chromatin helps to exclude water, and thus fewer reactive oxygen species are generated near DNA as a result of irradiation.…”
Section: Glycosylasementioning
confidence: 99%